The relationships between career concerns and political tactics in organizations - Zanzi, Alberto [Verfasser]; Arthur, Michael B. [Verfasser]; Shamir, Boas [Verfasser] (My University, 1991)
"The study examined the relationships between four career concerns (Personal Success, Organizational Involvement, Skill Development and Autonomy) and two categories of political tactics in organizations (Hierarchical Tactics and Networking Tactics) in a sample of management school alumni. Career concerns were not related to the employment of hierarchical tactics but were strongly related to the use of networking tactics. 'External' career concerns of personal success and organizational involvement were more strongly related to political behavior than 'internal' career concerns of skill development and autonomy. Organization size was significantly related to the use of hierarchical tactics but not to the use of networking tactics. Type of organization structure (mechanistic versus organic) did not have a direct effect on political behavior but moderated the relationships between career concerns and political tactics. These relationships were stronger in organic than in mechanistic organizations." (author's abstract) ((en)) Der Beitrag befasst sich mit dem Verhältnis von Karrierebelangen und den in Organisationen verfolgten politischen Taktiken. Hierzu wurden die Absolventen einer amerikanischen Wirtschaftsschule befragt. Die Karriereziele wurden anhand der folgenden Faktoren erhoben: persönlicher Erfolg, Unternehmensverwirklichung, Qualifizierung und Autonomie. Für politische Taktiken wurden zwei Kategorien gebildet: hierarchische und vernetzende Taktiken. (IAB)
Die Beziehungen zwischen Karrierebelangen und politischen Taktiken in Unternehmen
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; S 1.3.3 Vollzeitschulische Berufsausbildung; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.4 Biografiegestaltung; Berufsverlauf; Wirtschaftsfachschule; Absolvent; Arbeitsverhalten; Berufserfolg; Berufsproblem